Zebrafish jam‐b2 Gal4‐enhancer trap line recapitulates endogenous jam‐b2 expression in extraocular muscles. Issue 12 (10th October 2015) - Matsui, Hideaki; Dorigo, Alessandro; Buchberger, Astrid; Hocking, Jennifer C.; Distel, Martin; Köster, Reinhard W.
Abstract : Background: Members of the junctional adhesion molecule (JAM) family function as cell adhesion molecules and cell surface receptors. The zebrafish genome contains six different jam genes, and jam‐b and jam‐c were shown to be essential for myoblast fusion during skeletal muscle development. However, little is known about jam‐b2 expression and function.Results: We isolated the cDNA of zebrafish jam‐b2 . jam‐b2 is expressed specifically in extraocular muscles (EOMs), jaw muscles, and pectoral fins in zebrafish larvae, but not in trunk muscles. The identified jam‐b2 expression pattern is supported by the analysis of a zebrafish Gal4‐enhancer trap line, in which the coding sequence of the transcriptional activator KalTA4 together with a Gal4‐dependent UAS‐mCherry expression cassette was inserted into the jam‐b2 locus. Intercrosses with an UAS:EGFP strain proves the possibility for targeting transgene expression to EOMs, jaw muscles and fins. Finally, we characterized the concerted contraction pattern of EOMs in larvae performing an optokinetic response.Conclusions: The expression pattern of jam‐b2 suggests that it may contribute different properties to EOMs, jaw muscles, and pectoral fins. The jam‐b2 :KalTA4‐UAS‐mCherry transgenic strain serves a dual role as both a reporter for these muscles and as a valuable genetic tool for targeting transgene expression to EOMs. Developmental Dynamics 244:1574–1580, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: jam‐b2 is expressed specifically in extraocular muscles (EOMs), jaw muscles and pectoral fins in zebrafish larvae, but not in trunk muscles. The jam‐b2:KalTA4 enhancer trap strain is a tool for targeting transgene expression to zebrafish EOMs. It will be useful for investigating the molecular mechanisms and physiology controlling eye movement as well as for addressing mechanisms of congenital neurological diseases.